Jeru's journey : the life and music of Gerry Mulligan - Josephson, Sanford (Hal Leonard jazz biography series., 2015)
In a career that spanned more than 50 years, Gerry Mulligan was revered and recognized as a groundbreaking composer, arranger, bandleader, and baritone saxophonist. His legacy comes to life in this biography, which chronicles his immense contributions to American music, far beyond the world of jazz. Mulligan's own observations are drawn from his oral autobiography, recorded in 1995. These are intermingled with comments and recollections from those who knew him, played with him, or were influenced by him, as well as from the author, who interviewed him in 1981. Gerry Mulligan: The Melody Lingers On vividly recounts all the major milestones and complications in Mulligan's extraordinary life and career, ranging from his early days of arranging for big bands in the 1940s to his chance 1974 meeting with Countess Franca Rota, who would have a major impact on the last two decades of his life. In between were his battles with drugs; his significant contributions to the historic 1949 Birth of the Cool recording; the introduction of an enormously popular piano-less quartet in the early 1950s; the creation of his innovative concert jazz band in the early '60s; his collaboration-personal and professional-with actress Judy Holliday; his breakthrough into classical music; and his love of and respect for the American Songbook.